Assessment of Microsatellite Instability in Endometrioid Carcinoma by Immunohistochemistry At Armed Forces Institute of Pathology, Rawalpindi - Arif, Ayesha; Akhtar, Farhan; Ahsan, Ahmed; Din, Hafeez Ud; Ahmed, Rabia; Ahmed, Aminah (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess microsatellite instability in endometrioid carcinoma by immunohistochemistry expression of MLH1, PMS2, MSH2 and MSH6.Study design: Case series.Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, from Jun to Dec 2018.Methodology: Thirty-two cases of endometrioid carcinoma were included in the study. Patient age and menopausal status were recorded. The grade of the tumour was ascertained by microscopic examination. Immunohistochemistry for MLH1, PMS2, MSH2 and MSH6 assessed microsatellite instability.Results: In our study, eight females (25%) had premenopausal status while 24 (75%) had postmenopausal status. Out of 32 cases, 25 (78.1%) females had grade-I tumours, 4 (12.5%) had grade-II tumours, and 3 (9.45%) had grade-III endometrioid carcinoma. MMR status was proficient in 8 cases (25%) while deficient in 24 cases (75%). Among the 24 cases of MMR deficient endometrioid carcinoma, loss of expression of MLH1 was most frequent n=15 (62.5%), followed by PMS2 n=14 (58.3%) MSH2 n=7 (29.2%). MSH6 was retained in all cases. The most common pattern was a combined loss of MLH1/PMS2 in 12 cases (50%).Conclusion: As depicted by the high percentage of MMR deficient tumours, microsatellite instability is observed in many endometrioid carcinomas. Patients suffering from endometrioid carcinoma should be screened for Lynch syndrome by testing for MMR status.